PEMANFAATAN SAMPAH PLASTIK KEMASAN MENJADI TEMPAT TISU BERNILAI EKONOMIS DALAM KEGIATAN PKM: RESPON MASYARAKAT - Ebiranti Atakuni; Adely Indri Yonatan; Dwi Yurenza Pandango; Else Novita Rambu Rima; Herlian Rambu Kariri; Syaneta Elsa Rambu Wandal; Risma Puspita Sari Lawa Jati; Vidriana Oktoviana Bano; Riwa Rambu Hada Enda (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
This community service activity aims to utilize packaged plastic waste into tissue products that have economic value and to know the community's response to these products. The materials used are in the form of packaging plastic waste obtained from the surrounding environment, while the methods used include the preparation, implementation, and evaluation stages by involving 5 respondents as potential buyers. Data collection was carried out through questionnaires that included aspects of appearance, function, creativity, and economic value, then analyzed using quantitative descriptive techniques. The results and discussions show that the product where the wipes are successfully made with a simple process and has good use and aesthetic value. The majority of respondents gave a "agree" rating on all aspects, indicating that the product has high appeal, appropriate functionality, and creativity and is worth developing. In addition, the product has economic value because of its low production costs with the potential to profit from the difference in selling price. Thus, it can be concluded that the use of packaged plastic waste as a tissue holder is able to reduce environmental waste while providing business opportunities and increasing public awareness in creative and innovative waste management.